Practical Application of Biochar Fertilizer for Use in Rice Cultivation. 'One Ton per RaiI' Experiment in Eastern Thailand - Gordon Hirst (2019)
© 2018 Asian Institute of Technology. Biochar is produced by direct thermal decomposition of biomass in the absence or restriction of oxygen (preventing combustion), a process known as pyrolysis. This produces high-carbon, fine-grained charcoal like substance. Biochar is promoted primarily as a soil amendment and has the potential to dramatically increase crop yields. In addition to this, it offers numerous environmental benefits including:•GHG reduction in both from the supply (production) and demand (application), through carbon sequestration•Adsorption of soil toxins•Improved soil health by increasing organic matter (SOM)•Resolving localized biomass waste issuesWith the potential of increased crop yields and multitude of environmental benefits, biochar application would appear to be an obvious agricultural practice, however, it has still to create traction as a viable agricultural system. This is due, in part, to the large dosage rates required and consequently higher application costs when compared with the use of synthetic fertilizers. A plausible resolution to this is through technology adaption, specifically the development of 'low dose, high-efficiency biochar fertilizers', based on nano-structures and soluble components. The rationale behind of these biochar-based fertilizers is to increase the redox potential (Eh), by reducing from a mineral into a biochar substrate. The concept is that Eh and pH are respectively and jointly major drivers of soil/plant/microorganism systems.